Social Protection Response to the COVID-19 Crisis in the Dominican Republic - World Bank (World Bank, Washington, DC, 2021)
The Government of the Dominican Republic (DR) adopted a series of economic and social measures to protect households and businesses and prevent employment losses as a response to the Coronavirus disease SARS-CoV-2 (COVID-19) health and economic crisis. Social protection policies and programs have been used globally as effective mechanisms to respond to the economic crisis due to the COVID-19 pandemic. This policy note aims to document and analyze the design and implementation of the three main cash-transfer programs that the government used to protect households and workers affected by the COVID-19 crisis. The programs that are part of the scope of the note are: (1) stay at home (quédate en casa, QEC), (2) the employee solidarity assistance fund (fondo de asistencia solidaria del empleado, FASE), and (3) the independent worker assistance program (programa de asistencia al trabajador independiente, PA’ TI). The analysis of these programs is based on a desk review of administrative and legal documents, media information, program reports, and operational rules. The policy note is organized as follows: first, it provides an overview of the impact of COVID-19 on the economy and identifies the potentially affected population. Second, it provides a description of the design and implementation of the three social protection programs and their expenditures. Finally, it discusses lessons learned, including challenges and opportunities to improve social protection policies, based on an adaptative social protection framework.